An experimental and modelling study of selected heavy metals removal from aqueous solution using Scylla serrata as biosorbent - Aris, Ahmad Zaharin; Ismail, F. A.; Ng, Hui Yin; Praveena, Sarva Mangala (Universiti Putra Malaysia Press, 2014)
This study was conducted using crab shells as a biosorbent to remove Cu and Cd with different initial concentrations of 1, 5, 10, 15, and 20 mg/L in a biosorption treatment process. Crab shells were selected as biosorbents due to their abundance in the environment and ready availability as waste products from the market place. This study aimed to determine the ability of Scylla Serrata shells to remove Cu and Cd in an aqueous solution, as well as to provide a comparison of the removal rate between the two metals. The data were incorporated into hydrochemical software, PHREEQC, to investigate the chemical speciation distribution of each heavy metal. The shells of S. Serrata were found to have a significant (p<0.05) ability to remove Cu and Cd following the treatment. After six hours of treatment, the crab shells had removed 60 to 80% of both metals. However, the highest removal percentage was achieved for Cu with up to 94.7% removal rate in 5 mg/L initial Cu concentration, while 85.1% of Cd was removed in 1 mg/L initial solution, respectively. It can be concluded that the shells of S. Serrata could remove Cu and Cd better with significant results (p<0.05) in 1 and 5 mg/L initial concentrations, respectively.